I just don't like the sound of no! - Cook, Julia, 1964-; De Weerd, Kelsey (Boys Town, NE : Boys Town Press, 2011)
Shows readers the steps to the fundamental social skills of accepting "no" and disagreeing appropriately. When RJ learns to use these skills the right way, he finds that rewards come his way, instead of arguments.
"My story about accepting 'no' for an answer and disagreeing ... the right way!"--Cover.
2.1
K-3
K-3
Keywords: Children -- Life skills guides -- Juvenile fiction; Conflict (Psychology) -- Juvenile fiction; Frustration -- Juvenile fiction; Interpersonal communication -- Juvenile fiction; Obedience -- Juvenile fiction; Conflict (Psychology) -- Fiction; Frustration -- Fiction; Interpersonal communication -- Fiction; Life skills -- Fiction; Obedience -- Fiction; Communication -- Fiction; Conflict (Psychology) -- Fiction; Frustration -- Fiction; Life skills -- Fiction; Obedience -- Fiction; Picture books for children